Genomic diversity and genome-wide association analysis related to yield and fatty acid composition of wild American oil palm. (March 2021) - Ithnin, Maizura; Vu, Wendy T.; Shin, Min-Gyoung; Suryawanshi, Vasantika; Sherbina, Katrina; Zolkafli, Siti Hazirah; Serdari, Norhalida Mohamed; Amiruddin, Mohd Din; Abdullah, Norziha; Mustaffa, Suzana; Marjuni, Marhalil; Nookiah, Rajanaidu; et al.
Highlights: RAD sequencing of E. oleifera and E. guineensis. GWAS analysis detected SNPs associated with fatty acid composition and yield traits. Potential use of E. oleifera in developing sustainable oil palm. Individual palms with a cumulative 90 % of variation, identified for conservation. Abstract: Existing Elaeis guineensis cultivars lack sufficient genetic diversity due to extensive breeding. Harnessing variation in wild crop relatives is necessary to expand the breadth of agronomically valuable traits. Using RAD sequencing, we examine the natural diversity of wild American oil palm populations (Elaeis oleifera), a sister species of the cultivated Elaeis guineensis oil palm. We genotyped 192 wild E. oleifera palms collected from seven Latin American countries along with four cultivated E. guineensis palms. Honduras, Costa Rica, Panama and Colombia palms are panmictic and genetically similar. Genomic patterns of diversity suggest that these populations likely originated from the Amazon Basin. Despite evidence of a genetic bottleneck and high inbreeding observed in these populations, there is considerable genetic and phenotypic variation for agronomically valuable traits. Genome-wide association revealed several candidate genes associated with fatty acid composition along with vegetative and yield-related traits. These observations provide valuable insight into the geographic distribution of diversity, phenotypic variation and its genetic architecture that will guide choices of wild genotypes for crop improvement.